Research of the influence of sinter production processes on rail transport performance (Transport systems and technologies, 2019)
At modern metallurgical enterprises, as a rule, railroad trains are used as the main technological transport. With their help, the movement of raw materials between the workshops is ensured, which ensures the continuity of the technological process. The article deals with the stages of work of metallurgical enterprises from the receipt of orders to the development of production plans. Blast furnaces and sinter plants have been selected as research sites. The factors influencing the production of pig iron in the domain shop are presented. The influence of stops of agglomeration equipment on the work of transport moving between the sections is highlighted. The STATISTICA software product was selected as the medium for analyzing the idle time of the agglomeration equipment, using the comparison between the empirical and theoretical distribution using the Pearson criterion. A conclusion was made on the consistency of their distribution. The analysis of the characteristics of the sintering machines as one of the tasks of the theory of mass service is carried out. Conclusions are made regarding the time spent on repairs and the possible refusal of each car in the prescribed period. The necessity of taking into account scheduled and extraordinary repair works at the sinter plant and their influence on the transportation of the finished sinter to the blast-furnace shop was determined.
Keywords: agglomeration machine, planning, observation, exponential distribution, mass service theory, flow intensity, repair